The Impact of the Width of the Tracking Area on Speckle Tracking Parameters-Methodological Aspects of Deformation Imaging. - Stoebe, Stephan; Tarr, Adrienn; Pfeiffer, Dietrich; Hagendorff, Andreas (Echocardiography, 2014)
Aims The aim of this study was to analyze the impact of the tracking area width on myocardial wall motion and deformation parameters in 2D speckle tracking. Methods and Results Standardized apical views were acquired in 30 healthy subjects and 15 patients with left ventricular systolic dysfunction using 2D echocardiography. Longitudinal peak systolic strain ( PSS), longitudinal peak systolic strain rate ( PSSR), postsystolic index ( PSI), peak longitudinal ( PLD), and peak transverse displacement ( PTD) were determined by 2D speckle tracking to analyze the impact of the tracking area width on global and regional myocardial wall motion and deformation parameters. The dimension of the tracking area has a significant impact on all parameters. With increasing width of the tracking area higher values of PSS, PSSR, PSI, and lower values of PLD and PTD were determined. With increasing width of the tracking area a significant number of segments were not tracked. In summary, especially global PSS is significantly influenced by the width of the tracking area. Conclusions The strain values determined by 2D speckle tracking are significantly influenced by the tracking area width. The tracking of the subendocardial layers only results in lower global strain values than tracking the complete ventricular wall using the medium or wide tracking area widths. The tracking quality in the far field is worse if the tracking area is too wide. The present data show that standard and reference values of deformation imaging should include detailed information about the position and the width of the tracking area.